Identifying potential conflicts between norms in contracts - Aires, João Paulo de Souza (2015)
Contracts formally represent agreements between parties and often involve the exchange of goods and services. In contracts, norms define the expected behaviors of the parties using deontic statements, such as obligations, permissions, and prohibitions. However, norms may conflict invalidating themselves and producing a contract inconsistency. A conflict arises when two or more norms are applied to the same context but have different deontic statements, such as permissions x obligations and prohibitions x obligations. The identification of such conflicts is often made by humans, which makes the task time consuming and error-prone. In order to automate such identification, in this work we propose an approach to identify potential conflicts between norms in contracts written in natural language. We build a two-phase approach that extracts norms and norm elements from contracts, creating a norm representation that we use to compare norms and identify potential conflicts. We evaluated the approach using a corpus of contracts with norm conflicts inserted, and we measured the accuracy for different cases of conflict, which resulted on values higher than 70%.